UX Heuristic evaluation of cross-channel interaction systems: first experimentations (Human Factors in Design, 2020)
This is the first experimentation using the 9 UX heuristics (Renzi 2016) as a guide for a cross-channel system ecology heuristic evaluation. The paper presents the preparations, proceedings and results of the Airbnb system ecology UX evaluation, permeating three digital devices – smartphone, desktop computer and tablet – in order to simulate a cross-channel user experience journey in four micro-moments.